Job Stress, Role Expectation Conflict, Co-Worker Support, and Work-Life Balance among Muslimah Scholars: A Study in the Indonesian Historical Women Political Movement Members - Siti Mahmudah; Sadari Sadari; Ummah Karimah; Habib Shulton Asnawi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2022)
Women ulama or Muslimah scholars are ordinary people who experience role conflicts, problems with co-worker support, and work-life imbalances which would cause stress in the workplace. Some pieces of literature have examined these issues; however, a study in a specific community like Muslimah scholars who are Indonesian Women's Ulama Conference members (KUPI) is still limited. This study examines the effect of role conflict, co-worker support, and work-life balance on work stress among Indonesian female Ulama. The author uses a quantitative approach with a cross-sectional design. After filling out a consent form, data was collected from Muslimah scholars and members of KUPI. Participants then filled out the questionnaire by self-report. The results showed that most participants had moderate role expectation conflict, co-worker support, work-life balance, and job stress. The variables of role expectation conflict, co-worker support, and work-life balance influence work stress simultaneously. The indirect effect analysis showed only role expectation conflict on job stress through work-life balance, which has a significant effect. This finding indicates that although these women scholars have strategic careers and positions in their workplace, colleagues and family are two crucial things for them.